In vitro Antibacterial Efficacy of Bidens pilosa, Ageratum conyzoides and Ocimum suave Extracts against HIV/AIDS Patients’ Oral Bacteria in South-Western Uganda - Ezeonwumelu, Joseph Obiezu Chukwujekwu; Ntale, Muhammad; Kasozi, Keneth Iceland; Byarugaba, Frederick (Pharmacology & Pharmacy, 2017)
The objective of the study was to determine the antibacterial efficacy of Bidens pilosa Aqueous (BPA), Bidens pilosa Ethanolic (BPE), Ageratum conyzoides Aqueous (ACA), Ageratum conyzoides Ethanolic (ACE), Ocimum suave Aqueous (OSA) and Ocimum suave Ethanolic (OSE) extracts on HIV/AIDS patients’ oral bacteria. Healthy green leaves of the plants were collected in Ishaka Uganda, processed and portions separately extracted with hot distilled water and cold ethanol. The susceptibility, MIC and MBC of each extract were determined using standard protocols. The bacteria had significant (p < 0.05) respective total susceptibilities of 35 [28.7%] to BPA; 42 [34.4%] to BPE; 61 [50.0%] to ACA; 45 [36.9%] to ACE; 38 [31.1%] to OSA; 32 [26.3%] to OSE; 105 (86.0%)] to ceftriaxone. BPE, ACA, OSA, OSE and ceftriaxone had significant MIC with [F(1, 13); P = 0.00 and BPA with F(1, 13); P = 0.03]. BPE, ACA, ACE, OSA and ceftriaxone had significant MBC with [F(1, 13); P = 0.00 and BPA with F(1, 13); P = 0.01] on the test bacteria (MANOVA). These tested medicinal plants’ extracts and ceftriaxone had significant activity against oral bacteria with ACA having the best activity when compared with the control. However, the plants’ extracts were resisted by some of the bacteria. These findings validate the claims of efficacy of Bidens pilosa, Ageratum conyzoides and Ocimum suave on oral lesions of HIV/AIDS patients made by traditional healers and local people in South-Western Uganda. We recommend a detailed study of structural identities and activities of the active antibacterial principle(s) in these plants for possible new drug entities and verification of the interactive effects of the principle(s) with ARVs and cotrimoxazole used daily by HIV/AIDS patients.
Keywords: Antibacterial Efficacy, Bidens Pilosa, Ageratum Conyzoides, Ocimum Suave, Oral Bacteria, HIV/AIDS, Uganda